2001
DOI: 10.1902/jop.2001.72.6.788
|View full text |Cite
|
Sign up to set email alerts
|

The Dento‐Epithelial Junction: Cell Adhesion by Type I Hemidesmosomes in the Absence of a True Basal Lamina

Abstract: The results indicate that the epithelium-tooth interface is a unique structure wherein epithelial cells adhere by means of bona fide hemidesmosomes to an epithelium-derived extracellular matrix lacking most of the common BM components. Moreover, TF cells differ from connective tissue facing (CTF) cells, not only by their cell surface molecules and their production of extracellular matrix, but also by their cytoskeletal architecture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 44 publications
3
69
0
Order By: Relevance
“…The JE adheres to the tooth surface, and seals off periodontal tissues from the oral environment. It is formed initially by fusion of the reduced enamel epithelium with the oral epithelium (20), and is connected to the enamel via an inner basal lamina and hemidesmosomes (22). Two proteins, AMTN and ODAM/APIN, have been identified in the JE (9)(10)(11).…”
Section: Discussionmentioning
confidence: 99%
“…The JE adheres to the tooth surface, and seals off periodontal tissues from the oral environment. It is formed initially by fusion of the reduced enamel epithelium with the oral epithelium (20), and is connected to the enamel via an inner basal lamina and hemidesmosomes (22). Two proteins, AMTN and ODAM/APIN, have been identified in the JE (9)(10)(11).…”
Section: Discussionmentioning
confidence: 99%
“…Our data revealed that NaF at low concentration invariably increases fibronectin in epithelial cells. Human gingival epithelial cell expresses several laminin-binding integrin receptors (15)(16)(17)20). During the healing of mucosal wounds in vivo, oral keratinocytes first secrete laminin-5 into their extracellular matrix, and start to deposit matrix-bound laminin α5 chain only after they have stopped migrating (3,12).…”
Section: Discussionmentioning
confidence: 99%
“…Several cell types have been identified within gingival connective tissue, and gingival fibroblasts, which account for most connective tissue cells, are likely to be responsible for the constant functional adaptation of gingival connective tissue (15). The structural composition of the epithelial-connective tissue interface is influenced by interactions between epithelial cells and fibroblasts.…”
mentioning
confidence: 99%
“…In contrast, the junctional epithelium is structurally and functionally unique. Namely, the junctional epithelium is located at a strategically important interface between the gingival sulcus and the underlying soft and mineralized connective tissues of the periodontium (Hatakeyama et al, 2006, Hormia et al, 2001, contains a nonkeratinizing epithelial layer at the free surface. The gingival epithelium, in particular, the junctional epithelium is highly porous and the epithelial cells are interconnected by a few desmosomes and the occasional gap junction, resulting in wider intercellular spaces that may provide a pathway for fluid and transmigrating leukocytes from the gingival connective tissue to the gingival sulcus (Hashimoto et al, 1986, Bosshardt & Lang 2005, Hatakeyama et al, 2006, and even for microorganisms moving in the opposite direction (Bosshardt & Lang 2005, Darveau, 2010, Darveau et al, 1997, Marra & Isberg, 1996, Page & Schroeder, 1976, Tonetti et al, 1998.…”
Section: Periodontal and Pulpar Tissues Under Homeostatic Conditionsmentioning
confidence: 99%